Strategies for Development of Palliative Care From the Perspectives of General Population and Health Care Professionals: A Japanese Outreach Palliative Care Trial of Integrated Regional Model Study. (September 2015) - Yoshida, Saran; Miyashita, Mitsunori; Morita, Tatsuya; Akizuki, Nobuya; Akiyama, Miki; Shirahige, Yutaka; Ichikawa, Takayuki; Eguchi, Kenji
This study primarily aimed to identify future actions required to promote palliative care in Japan. The future actions regarded as effective by the general population were "improve physicians' skill in palliative care" (61%), "create a counseling center for cancer" (61%), and "improve nurses' skill in palliative care" (60%). In contrast, future actions regarded as effective by the health care professionals were "set up a Web site that provides information about cancer" (72%), "promote consultation with specialists in palliative care" (71%), and "open an outpatient department specializing in palliative care" (70%). The results suggest (1) development and maintenance of settings; (2) enhancement of palliative care education and training programs for health care providers; and (3) improvement in distributing information about cancer and regional palliative care resources to the general population.